To correlate the knowledge and attitude regarding child labour among adults of rural and urban area in Wardha district - G. Moon, Priyadarshani (International Journal of Nursing Research, 2023)
Background: The term child labour is used for employment of children below a certain age which is considered illegal by law and custom. Material and Method: Non– Probability Convenience sampling using in 200 rural and 200 urban areas, a structured questionnaire and an attitude scale. Result: Mean knowledge score of rural area was 11.64±2.90 and a mean percentage score of 38.80±9.68, mean knowledge score of urban area was 17.49±2.88 and a mean percentage score of 58.30±9.60. Mean attitude score of rural area was 64.32±5.78 and a mean percentage score of 53.60±4.82, mean attitude score of urban area was 68.03±5.72 and a mean percentage score of 56.69±4.77.overall the knowledge of the adults was good and attitude showing negative correlation. Adult‟s age in rural area is statistically associated with knowledge scores. Monthly family income (Rs), in rural area is statistically associated with knowledge scores. Thus the H1 is accepted. Conclusion: Significant negative correlation was found between knowledge and attitude score in rural area (Correlation r= -0.20, p-value=0.003), and urban area (Correlation r= -0.15, p-value=0.029). it is finding of the observations are this significance is applied at 5% level of significance shows of knowledge scores of rural and urban area.